Detection of group a human rotavirus G9 genotype circulating in Córdoba, Argentina, as early as 1980 - Barril, Patricia Angelica (2006)
The incidence of human rotavirus G types wasdetermined over a 25-year period (1979–2003) byusing reverse transcription-PCR (RT-PCR) toexamine 519 stool specimens found to bepositive for rotavirus by enzyme linked immunosorbentassay (ELISA) or polyacrylamide gelelectrophoresis (PAGE). These stool sampleswere obtained from children under 3 years oldwho had been treated for acute diarrhea at publichospitals in Co´ rdoba, Argentina. The presentstudy describes the continued circulation of thecommon human G types G1 (53.8%), G2 (10.2%),G3 (4.4%), and G4 (27%), and also the detection ofthe unusual types G8 (0.5%) and G9 (4.2%).Genotype G9 was detected during the 1980–1988 and 1997–2003 periods at relatively lowrates. Rotavirus G types distribution was independentof age (1–18 months), gender or outpatientor in-patient status. Unexpectedly, 44.6%of mixed infections were detected, involvingcommon and unusual genotypes. Overall,95.4% of the typed strains belonged to the mostprevalent human serotypes (G1–G4) but thedetection of G9 infection throughout this studyperiod highlights the importance of this serotypeas a human pathogen.